A framework for determining and prioritizing relational capitals: The case of Iran e-business. Issue 2 (27th May 2014) - Ghane, Soheila; Akhavan, Peyman
Abstract : Purpose: – The purpose of this study is to propose a framework to determine and prioritize relational capitals. This study has empirically performed the framework and revealed prioritized indicators of relational capital within service and non-service industries in Iran. Design/methodology/approach: – A valid questionnaire was utilized to conduct a survey of 243 business managers in different organizational levels of service and non-service industries in Iran. Findings: – Correlation analysis was utilized to ascertain validity of measures. Priority of each relational capital was specified using ordinal regression analysis. Research limitations/implications: – The findings offer valuable insights on relational capital and its indicators in a novel perspective. Practical implications: – Using the proposed framework and utilizing the classification of relational capital indicators, managers and analysts will be able to enumerate the most effective factors for improving business performance and competitive authority based on types of business relations and its environment. Originality/value: – This study provides a guideline for determining and prioritizing business relational capital considering both sides, business-to-business and business-to-consumer relations, which have been under examination in the literature.